Implementation of Merdeka Curriculum for diagnostic assessment in senior high schools - Angelika, Neindea; Setiawan, Deni (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2023)
This study aims to analyze in depth the process of implementing an independent curriculum at the learning planning stage based on the results of diagnostic assessments in realizing learning outcomes that are in accordance with the needs and characteristics of students. This research uses a qualitative method with a case study approach. Data collection techniques were conducted through literature studies and interviews with two resource persons. The data analysis technique used an interactive model, which according to Miles and Hubermen through data reduction, presentation, and conclusion. The results showed that the implementation of an independent curriculum through the implementation of diagnostic assessments was less than optimal in achieving learning objectives due to various factors, so the implementation of an independent curriculum currently still requires regular socialization, training, and assistance from every education stakeholder from both the government and the community.